Data Reconciliation of Low Grade Ores and Trace Elements - Gold Balance of Vammala Concentrator. Issue 17 (2015) - Tommiska, J.; Remes, A.; Vähäkangas, V.
Abstract: Data reconciliation methods are required for setting up reliable mass balances of concentrator plant circuits. The balances are used for daily reporting and also as a preceding work phase prior to process modeling. Balancing of circuits with low grade assays, such as gold, where the concentration can be only less than one parts per million - and flow rates and slurry densities varies largely stream by stream - can form mathematically awkwardly defined solving problem. This paper presents a robust data reconciliation algorithm to calculate the low grade mass balances reliably. Advantages of this method are shown with process sampling based mass balancing of the Vammala concentrator gold flotation circuit.